Reinterpreting Ritual Purity in the City: Fiqh Sosial Perspectives on Pet Dog Ownership among Shafi‘i Communities in Contemporary Egypt - Sukataman Sukataman; Agung Nugroho Reformis Santono; Idlofi Idlofi; Umar Chamdan; Muchamad Amien; Muhammad Agus Salim (Santri: Journal of Pesantren and Fiqh Sosial, 2026)
Urbanization and modern lifestyles in Cairo, Egypt, have transformed the interaction between Muslims, predominantly Shafi'i adherents, and dogs, which are traditionally considered strictly impure (najāsah mughallaẓah). This study explores this social shift using a socio-legal approach and the Fiqh Sosial (Social Fiqh) perspective of KH. M.A. Sahal Mahfudh. Data were collected through field observations in Cairo and an analysis of contemporary fatwas issued by Dār al-Iftāʾal-Miṣriyyah. The results show that the dense urban spatial reality and ecological metabolism of the metropolis create an unavoidable situation (ʿumūm al-balwā). Consequently, Shafi'i adherents pragmatically negotiate this hardship by adopting the Maliki school's view, which regards living dogs as pure. This practice of inter-madzhab concession (rukhṣah) is institutionally legitimized by Dār al-Iftāʾ, which formally allows dog ownership for specific needs and suggests the Maliki ruling to relieve public anxiety (waswas). The study concludes that Islamic law in contemporary Egypt functions not as rigid orthodoxy, but as a flexible, problem-solving instrument that accommodates cultural dynamics and public interest (maṣlahah), fostering an inclusive ecological harmony in public spaces.